PENERAPAN MODEL PEMBELAJARAN ARIAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN NEGOSIASI SMKN1 PONTIANAK - Putra, Ridho Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem in this study is the low learning outcomes of students on the negotiations subjects of eleventh grade class of Marketing 1 class of SMKN 1 Pontianak. The purpose of this study is to improve the learning process to improve students? learning outcomes in the negotiation subjects of by using ARIAS learning model (Assurance, Relevance, Interest, Assessment, and Satisfaction). The method used is a classroom action research which consisting of four stages: (a) planning, (b) implementation, (c) observation, (d) reflection. Data were collected through observation sheet and student learning result through pretest and posttest. This study was conducted in two cycles. The results showed an increase in student learning outcomes. This is evident from the results of research cycle I where the average value of student learning outcomes increased from 50 to 71.36, and mastery of student learning outcomes increased from 18.18% to 66.67%. Then the results of research cycle II, the average value of student learning outcomes increased from 54.85 to 76.06, and completeness of student learning outcomes increased from 24.24% to 81.82%. From the data obtained, it can be seen that there is an increase in student learning outcomes in cycles I and II. Thus, research using ARIAS learning model (Assurance, Relevance, Interest, Assessment, and Satisfaction) in negotiation learning can improve students? learning result of eleventh grade class of Marketing 1 class of SMKN 1 Pontianak and improve teacher?s ability in applying of learning model in class.Keywords: ARIAS Learning Model (Assurance, Relevance, Interest, Assessment, Satisfaction), Negotiation Subject, and Learning Outcomes.